Interprofessional education and collaboration an evidence-based approach to optimizing health care - Hamson-Utley, Jennifer Jordan; Mathena, Cynthia Kay 1963-; Gunaldo, Tina Patel 1972- (Human Kinetics, Inc., 2021)
"This book is written for educators (in academia or clinical practice), health professionals, and health administrators who are interested in learning more about an interprofessional approach to improving patient and community outcomes. It provides a foundational base for interprofessional education (IPE) and interprofessional collaborative practice (IPCP). Each chapter is filled with evidence-based information substantiated by numerous references from various resources and multiple professions."